The Relationship Between Vitamin B6, Diabetes and Cancer - Merigliano, Chiara; Mascolo, Elisa; Burla, Romina; Saggio, Isabella; Vernì, Fiammetta (Frontiers in Genetics, 2018)
Pyridoxal 5’-phosphate (PLP), the active form of vitamin B6, works as cofactor in numerous enzymatic reactions and it behaves as antioxidant molecule. PLP deficiency has been associated to many human pathologies including cancer and diabetes and the mechanism behind this connection is now becoming clearer. Improper intake of this vitamin increases the risk of many cancers; furthermore, PLP deprivation impairs insulin secretion in rats, whereas PLP supplementation prevents diabetic complications and improves gestational diabetes. Growing evidence shows that diabetes and cancer are correlated not only because they share same risk factors but also because diabetic patients have a higher risk of developing tumors, although the underlying mechanisms remain elusive. In this review, we will explore data obtained in Drosophila revealing the existence of a connection between vitamin B6, DNA damage and diabetes, as flies for the past decade turned out to be a promising model also for metabolic diseases including diabetes. We will focus on recent studies that revealed a specific role in maintaining chromosome integrity and glucose homeostasis for PLP and we will show that these aspects are correlated. In addition, we will discuss recent data identifying PLP as a putative linking factor between diabetes and cancer.